"Фантазеры" и другие рассказы: [для среднего школьного возраста] / Николай Носов - Носов Николай Николаевич (Яркая ленточка, 2020)
Экземпляры: ф.6 (20210311) / Инвентарный номер: 3583 И / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Н 84 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44